Examining the Dialectics of Positivism and Logical Positivism in Philosophy at the University Level - Yullian Rachmat Yudhi Sentausa; Mia Tanti Annisa; Dede Sunaryati; Tri Anita; Rina Hidayati Pratiwi (el-Nizami : Jurnal Manajemen Pendidikan, 2026)
This study aims to conduct an in-depth literature review on the paradigmatic and dialectical transition between classical positivism and logical positivism in the scientific structure of higher education. Positivism , pioneered by Auguste Comte, positions the scientific method as the sole means of understanding reality through empirical observation . The evolution of this paradigm towards neopositivism by the Vienna Circle shifted the academic focus to formal language analysis , the rigor of mathematical logic , and the principle of strict verification. The research method used is a qualitative literature study with a descriptive-analytical approach that refers to the standard methodology of literature review from John W. Creswell. The results of the discussion show that the dialectic of these two schools of thought results in the standardization of research methodology in higher education that is quantitative and value - free (value-free science). However , this dominance has sparked criticism from Karl Popper 's critical rationalism and Thomas Kuhn's paradigm theory . The study concludes that higher education must be able to maintain a dialectical space between scientific precision and humanities values in order to address the challenges of complex reality .